2021
DOI: 10.1103/physrevlett.127.097202
|View full text |Cite
|
Sign up to set email alerts
|

Supermagnonic Propagation in Two-Dimensional Antiferromagnets

Abstract: We investigate the propagation of magnons after ultrashort perturbations of the exchange interaction in the prototype two-dimensional Heisenberg antiferromagnet. Using the recently proposed neural quantum states, we predict highly anisotropic spreading in space constrained by the symmetry of the perturbation. Interestingly, the propagation speed at the shortest length scale and timescale is up to 40% higher than the highest magnon velocity. We argue that the enhancement stems from extraordinary strong magnon-m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 57 publications
5
16
0
Order By: Relevance
“…[ 49,50 ] NQS found applications in studying ground states and low‐energy states, [ 51–55 ] quantum state tomography, [ 56 ] simulating open quantum systems, [ 50,57–61 ] and real‐time evolution. [ 30,31,62–65 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 49,50 ] NQS found applications in studying ground states and low‐energy states, [ 51–55 ] quantum state tomography, [ 56 ] simulating open quantum systems, [ 50,57–61 ] and real‐time evolution. [ 30,31,62–65 ]…”
Section: Methodsmentioning
confidence: 99%
“…Typically, NQS are time propagated using time-dependent variational Monte Carlo (t-VMC) [8,40,41]. So far, this has been studied in the literature primarily in the context of quenches in the spin-1/2 Ising and Heisenberg models in both one and two dimensions [42][43][44][45][46][47]. In many cases, achieving numerical stability has been identified as the key challenge for the reliable simulation of quantum dynamics [42][43][44] and also for ground state optimization using imaginary time propagation [19].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we take a closer look at dynamics in the antiferromagnetic 2D Heisenberg model, which has previously been studied with t-VMC on a 2D square lattice geometry. There, stable time propagation has been demonstrated using the well-established restricted Boltzmann machine (RBM) architecture [45][46][47]. We compare this setting to the same Hamiltonian on a two-leg (L × 2) ladder geometry, which features significantly more complex quantum dynamics and which we find to be much more sensitive to numerical instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…These have a frequency solely determined by the exchange interactions and can be as high as few tens of THz, having at the same time wavelength down to the subnanometer range. Recently, femtosecond dynamics of pairs of these high-energy magnons have been observed and addressed theoretically [32][33][34][35][36] , revealing unique features such as high entanglement between magnons 32,36 and coherent control of longitudinal oscillations of the AFM vector 33,34 . However, ways to employ such magnons to achieve switching at the femtosecond timescale have, to the best of our knowledge, not been discussed so far.…”
Section: Introductionmentioning
confidence: 99%
“…where Ŝi = Ŝ(r i ) are spin-1/2 operators, with r i = (x i , y i ), J ex is the exchange interaction (J ex > 0) and • restricts the sum to nearest neighbours. Recent studies on this model have shown that impulsive 32,34 and quench-like 35,36 perturbations of the exchange interaction lead to coherent oscillations of magnon pairs. Here we focus on parametric oscillations which can be excited by periodic modulation of exchange interactions by THz field transients [40][41][42] and optical pulses [32][33][34] described by…”
Section: Introductionmentioning
confidence: 99%